The cristera woman in Michoacán, 1926-1929 - Quezada Quiroz, Claudia Julieta (Universidad Pedagógica y Tecnológica de Colombia, 2012)
The aim of this current paper is to highlight the michoacanas women’s presence and involvement during the armed conlict between city-state and Catholic Church in México in the irst half of the XX century. It was known as the Cristeros war. The paper aims to point out the value that women played in that rebellion not only as irearm, munition and news providers among the different rebellious groups but also as importantentities in the conservation and clandestine practice characteristic of the catholic worship. Thus, the paper intends to ind out what the personal and social drivingforces of those women were to act in favour of the war no matter the consequences.